1997
DOI: 10.1038/nm1197-1280
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of a CFTR premature stop mutation in a bronchial epithelial cell line

Abstract: Cystic fibrosis (CF) is caused by mutations in the CF transmembrane conductance regulator (CFTR) protein. While 70% of CF chromosomes carry a deletion of the phenylalanine residue 508 (deltaF508) of CFTR, roughly 5% of all CF chromosomes carry a premature stop mutation. We reported that the aminoglycoside antibiotics G-418 and gentamicin can suppress two premature stop mutations [a stop codon in place of glycine residue 542 (G542X) and arginine residue 553 (R553X)] when expressed from a CFTR cDNA in HeLa cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
184
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(192 citation statements)
references
References 18 publications
7
184
0
1
Order By: Relevance
“…Therefore, we analyzed the nucleotide context of the responsive patients and found that fibroblasts that were responsive to treatment carried PTC mutations in a slightly different nucleotide background than previously reported (Table 3). Despite the small sample size of our study, the results presented herein suggest a hierarchy of stop codon readthrough treatment efficacy similar to that reported [20]: UAG≥UGA>UAA. Also, in agreement with Floquet et al [24] we found the same response pattern in nucleotides -1 and +4.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Therefore, we analyzed the nucleotide context of the responsive patients and found that fibroblasts that were responsive to treatment carried PTC mutations in a slightly different nucleotide background than previously reported (Table 3). Despite the small sample size of our study, the results presented herein suggest a hierarchy of stop codon readthrough treatment efficacy similar to that reported [20]: UAG≥UGA>UAA. Also, in agreement with Floquet et al [24] we found the same response pattern in nucleotides -1 and +4.…”
Section: Discussionsupporting
confidence: 83%
“…In the last few years, other potential strategies such as pharmacological chaperones [8], or the suppression of pathogenic nonsense mutations through the induction of translational readthrough have emerged [2,[9][10][11][12][13][14][15][16][17][18]. To this effect, aminoglycoside antibiotics such as gentamicin [16,17], and small molecules such as PTC124 [18] and NB84 [19], have been described to induce PTC readthrough, eluding the NMD mechanism and allowing the formation of stable mRNAs encoding for full-length mutant, but probably still quite active, proteins [20,21]. These products reduce proofreading of codon-anticodon recognition in the ribosome, allowing the suppression of PTCs and, as a general rule, the insertion of glutamine or tryptophan at premature UAG/UAA or UGA codons, respectively, occurs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Bedwell and co-workers 4,5 have also shown that G-418 and gentamicin can restore the expression of the cystic fibrosis transmembrane conductance regulator (CFTR) in a bronchial cell line with a nonsense mutation in the CFTR gene. Similarly, a Hurler syndrome fibroblast cell line heterozygous for a stop mutation showed a significant increase in alpha-L-iduronidase when cultured in the presence of gentamicin.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a Hurler syndrome fibroblast cell line heterozygous for a stop mutation showed a significant increase in alpha-L-iduronidase when cultured in the presence of gentamicin. 4,5 The strength of this approach was first demonstrated in vivo by the work of Barton-Davis and co-workers, who demonstrated that gentamicin could partially restore expression of fulllength dystrophin in mdx mice with the X-linked muscular dystrophy mutation (Mdm mdx ), a C-T transition at position 3185, resulting in a termination codon replacing a glutamine codon in the dystrophin gene. 6 Negamycin, a dipeptide antibiotic with similar stop codon-misreading activity, has also been shown to restore dystrophin synthesis in the mdx mouse skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have suggested that this strategy may be relevant for human diseases. Suppression of a nonsense mutation in the cystic fibrosis transmembrane conductance regulator gene by growth in gentamicin increased cystic fibrosis transmembrane conductance regulator expression by 10 to 20 % compared to control cells and restored cAMP-activated chloride transport [149,150]. In a mouse model of Duchenne muscular dystrophy, gentamicin was used to disrupt translational fidelity to phenotypically correct a nonsense mutation [151].…”
Section: Models Of Dravet Syndromementioning
confidence: 99%